Arktisk drama og biosofisk vitalisme: Knut Hamsuns dramatikk i lys av sjelelige landskap - Arntzen, Knut Ove (Nordlit, 2016)
In this article I try to define arctic drama in a concrete and metaphorical way by touching upon the dramatic oeuvre of Knut Hamsun. In Play of Life Hamsun plays with nature and the polar as topos. The drama, situated in a small market town in the Nordland area of northern Norway, uses coastal nature and culture as a framework. Nature is a driving force in this pre-expressive drama where the mythical enlightens the inner and symbolic dimension of human actions and spiritual conditions. This article will also show how nature is used to reflect the inner world of the characters. I will end with a look into the northern-Norwegian identity, the authorship of Hamsun, and the biosophical dimensions studied by the philosopher Peter Wessel Zappfe.
Keywords: Arctic Drama; Landscapes; Biosophical Vitalim; Scenic reception of Knut Hamsun; Spiral Dramaturgy